Assessment of macular function by multifocal electroretinography following epiretinal membrane surgery with internal limiting membrane peeling - Ji Won Lim (Dove Medical Press, 2010)
Ji Won Lim, Joon Hee Cho, Ha Kyoung KimDepartment of Ophthalmology, Hallym University Sacred Heart Hospital, Chuncheon, Republic of KoreaAbstract: The aim of the current study was to evaluate macular function before and after surgery for idiopathic epiretinal membranes with internal limiting membrane (ILM) peeling by means of multifocal electroretinography (ERG). Eighteen eyes of 18 patients who underwent vitrectomy with ILM removal were included. Best corrected visual acuity, optical coherence tomography (OCT), and multifocal electroretinography were assessed prior to surgery, and 3 and 12 months after surgery. All surgical samples were obtained and confirmed inclusion of an ILM by electron microscopy. Visual acuity and the central foveal thickness by OCT improved significantly 3 months postoperatively, with gradual recovery by 12 months. Preoperatively, only the P1 amplitude in rings 1 and 2 were decreased compared with the normal fellow eyes (P < 0.01). Three and 12 months after surgery, the P1 amplitude in rings 1 and 2 were decreased compared with the preoperative P1 amplitudes, but without significance. The photoreceptor status by OCT was related to the N1 amplitude before and after surgery. Although visual acuity and macular edema were improved after surgery, macular function, as indicated by multifocal ERG, had limited recovery at 12 months.Keywords: epiretinal membrane, macular function, multifocal electroretinography